A clinico-pathological study and management of cystic swellings of scrotum - Ruban, N. Prince Deva; Kumar, P. Naresh; Sekar, G. P. (International Surgery Journal, 2017)
Background: The cystic swellings of scrotum are one among the common surgical problem in all age group. Objective of this study is to identify the cause, mode of presentation, various modalities of treatment and outcome of these with least complications. Methods: A total of 100 cases of cystic swellings of scrotum fulfilling the methodology criteria’s were subjected to preformatted study. Final diagnosis was made with Clinical examination and Ultrasound. All 100 cases were treated surgically. Results: Most of the patients were in age group of 20-60 years (28%), presenting feature being scrotal swelling as a main complaint in 60% of cases, majority of them were right sided (64%), majority of them presented with in a year, 40% presented with in first 6 months and 30% in next 6 months. Primary vaginal hydrocele was the commonest cystic swelling (60%), followed by epididymal cyst, sebaceous cyst, haematocoele, pyocoele. Lord’s plication was the procedure, which was associated with early discharge of the patient and least post-operative complications. Most of the patients were discharged around 8th Post-operative day. Conclusions: Primary vaginal hydrocoele was the commonest cystic swellings of scrotum. Most of the cystic swellings were treated surgically with good results. Lord’s plication procedure was the least to have post-operative complication.